The meaningful interpretation of financial statements : the cause-and-effect ratio approach - Miller, Donald E. (New York : American Management Association, 1966)
This book deals with furnishing fundamental financial guidance to aid and encourage thoughtful analysis by businessmen
Includes bibliographical references and index.
oo 25/10/2018
Loans
Keywords: Financial statements